Thickness dependence of the anomalous Hall effect in thin films of the topological semimetal Co2MnGa - Markou, Anastasios; Kriegner, Dominik; Gayles, Jacob; Zhang, Liguo; Chen, Yi-Cheng; Ernst, Benedikt; Lai, Yu-Hong; Schnelle, Walter; Chu, Ying-Hao; Sun, Yan; Felser, Claudia (Physical Review B, 2019)
Topological magnetic semimetals promise large Berry curvature through the distribution of the topological Weyl nodes or nodal lines and further novel physics with exotic transport phenomena. We present a systematic study of the structural and magnetotransport properties of Co2MnGa films from thin (20 nm) to bulklike behavior (80 nm) in order to understand the underlying mechanisms and the role of topology. The magnetron sputtered Co2MnGa films are L21-ordered showing very good heteroepitaxy and a strain-induced tetragonal distortion. The anomalous Hall conductivity was found to be maximum at a value of 1138 S/cm, with a corresponding anomalous Hall angle of 13%, which is comparatively larger than topologically trivial metals. There is good agreement between the theoretical calculations and the Hall conductivity observed for the 80 nm film, which suggests that the effect is intrinsic. Thus, the Co2MnGa compound manifests as a promising material for topologically driven spintronic applications.
CRIS-Team Scopus Importer:2022-04-14